Bantuan Pangan Non Tunai dan Konsumsi Kalori Rumah Tangga Kabupaten Grobogan Jawa Tengah: Survei Sosial Ekonomi Nasional Maret Tahun 2021 - Arafih Firmansyah (Universitas Diponegoro, 2024)
This study aims to examine the impact of the non-cash food assistance program (BPNT), marital status, household size, the education level of the household head, and household expenditures on calorie consumption adequacy. The data used is secondary data from the 2021 National Socio-Economic Survey (Susenas) by the Badan Pusat Statistik, with a total of 28,453 households as the research sample. The variables include calorie consumption adequacy, receipt of the BPNT program, marital status, household size, the education level of the household head, and household expenditures. This study employs a quantitative descriptive method. Parameter estimation in logistic regression uses Maximum Likelihood Estimation (MLE), and the model is tested using the Hosmer and Lemeshow Goodness of Fit Test. The results show that the BPNT program, marital status, and the education level of the household head do not affect calorie consumption adequacy in Grobogan Regency. However, household size has a negative impact on calorie consumption adequacy, while household expenditures positively influence calorie consumption adequacy in Grobogan Regency.